Heavy metal content of tank goby (Glossogobius giuris) in East Segara Anakan, Cilacap, Central Java, Indonesia - Sulistiono Sulistiono; Yeni Irawati; Djamar T. F Lumban Batu (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Segara Anakan is a semi-close water ecosystem which is connected to Donan River (industrial and residential areas) in the east and Citanduy River (agricultural area) in the west. Most activity in those areas can produce a waste which becomes sources of harmful pollutants to the aquatic environment. The aim of this study was to analyze the content level of heavy metals (Pb, Hg, Cu and Cd) in muscle and safety level consumption of the tank goby (Glossogobius giuris) in the area. This study was conducted for 4 months in June, August, September and October 2017 at the waters of East Segara Anakan Lagoon of Cilacap (Central Java Province), The heavy metal concentration in the muscle was measured by AAS (Atomic Absorption Spectrophotometer). Based on the analysis, the heavy metal contents of Pb, Hg, Cu, and Cd in the tank goby were 0-0.005 mg/kg, 0-0.044 mg/kg, 0.164-0.293 mg/kg, and 0.001-0.032 mg/kg, respectively and these contents were under the safety limit. Safety level of consumption of the fish was 837.3  g/week (for adult) and 251.2  g/week (for children).